Liquid-filled projectile design. (Headquarters, U.S. Army Materiel Command : [U.S. G.P.O.], 1969)
" ... deals with the dynamics of liquid-filled projectiles which are known to behave in an unpredictable manner in flight."--Preface.
Cover title.
"April 1969."
Keywords: Projectiles.; Ammunition.; Ordnance.; Ballistics.; Projectiles, Aerial.; elektronické knihy; electronic books